Equipping medical students for ward round learning. (23rd May 2022) - Collett, James; Webster, Emma; Gray, Amy; Delany, Clare
Abstract: Background: While ward rounds offer a rich opportunity for learning, the environment is chaotic, and medical students can struggle to maximise this potential. Few studies have focused on the best way to equip students for ward round learning. One proposed tool developed to orient students' learning on the ward round is called the Seek, Target, Inspect and reflect, Closure and clerk (STIC) model. This study examines the effect of using this model on the student experience of ward round learning. Methods: Seven medical students with clinical attachments on medical wards in two rural hospitals in New South Wales, Australia, participated in three sequential focus groups over an 8‐week period. Students were asked about learning practices on ward rounds, what factors influenced their learning and how using the STIC model impacted on their experience. Thematic analysis was applied to focus group transcripts. Findings: Students valued learning opportunities from ward rounds but felt the learning potential was largely dependent on the team to which they were attached. Students reported the STIC model promoted greater agency and enabled them to be more self‐directed and able to negotiate the chaotic context. Students also valued the focus group discussions about their learning as an avenue to share and better understand their experiences of learning on ward rounds. Conclusion: Student experience of ward rounds can be influenced via (1) structured learning tools (STIC model) to better orient students and (2) facilitated discussions with peers to assist in developing skills of negotiating and directing one's own learning. Both should be more explicitly integrated in medical curricula.